Weiquan: the Chinese Civil Disobedience in a New Perspective - Tu, Alex (Thammasat Review, 2015)
This paper traces the development of the Chinese weiquan movement in the context of political and social changes in the late 20th and later 21st century China. I argue that thus far weiquan commentators have overemphasized it as a novel social phenomenon. I demonstrate that it is part of the political legacy of China’s past. Keywords: China, Rights Protection